Pengembangan Evaluasi Pembelajaran Bahasa Arab Berbasis Artificial Intelligence - Afifah, Anis (Kartika: Jurnal Studi Keislaman, 2025)
The aim of this research is to describe the Development, Feasibility and Effectiveness of Artificial Intelligence-based Arabic Language Learning Evaluation. This research uses the Research and Development (R&D) method using the ADDIE model. The results of this research and development are (1) evaluation of Artificial Intelligence-based Arabic language learning using Fusha Arabic. This product consists of 3 chapters whose contents contain major themes based on the existing RPS. Each chapter is equipped with vocabulary, material, learning videos, quizzes and practice questions. (2) based on the validation test results of material expert lecturers, it shows that in terms of material presentation, they received a score of 39 in the very valid category. Meanwhile, the validation test results from design expert lecturers obtained a score of 35 in the very valid category. The Arabic language teacher validation test results obtained a score of 74 in the very valid category. This teaching material is also effective because the results of the paired sample t-test show a significant number between the pre-test and post-test scores with a significant value (2-tailed) p= 0.000, <0.05.